2017
DOI: 10.1039/c7cy01398a
|View full text |Cite
|
Sign up to set email alerts
|

An efficient green protocol for the synthesis of tetra-substituted imidazoles catalyzed by zeolite BEA: effect of surface acidity and polarity of zeolite

Abstract: Zeolite BEA catalyzed synthesis of highly substituted imidazoles via a green approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…The mechanism are entirely consistent with previous literature. 27,32,33 The LADES@MNP has Lewis acidic on Zn atoms on the surface which can participate in the bonding with the oxygen atoms on the carbonyl groups to accept nucleophiles. Moreover, we believe that a partial contribution of the nanoparticles can facilitate a high active catalysis in our method because nano-support features have a good dispersion in the reaction mixture, just like a "quasi-homogeneous" catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism are entirely consistent with previous literature. 27,32,33 The LADES@MNP has Lewis acidic on Zn atoms on the surface which can participate in the bonding with the oxygen atoms on the carbonyl groups to accept nucleophiles. Moreover, we believe that a partial contribution of the nanoparticles can facilitate a high active catalysis in our method because nano-support features have a good dispersion in the reaction mixture, just like a "quasi-homogeneous" catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…[21][22][23][24] Various protocols for preparation of imidazoles via multicomponent reaction have been tested in literature, which employs a three-component reaction of 1,2-diketone or ketomonoxime, aldehyde, and ammonium acetate, or four-component reaction of 1,2-diketone, aldehyde, primary amines, and ammonium acetate. [25][26][27][28] Many of the synthetic approaches for the preparation of imidazoles suffer from one or more drawbacks such as drastic reaction conditions, low yields, by-products, prolonged reaction time, volatile organic solvent, tedious work-up processes, expensive and unrecyclable catalysts. [29][30][31][32] Thus, the development of efficient and environmentally benign catalysts is still highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Giaya et al demonstrated that the hydrophobicity of the dealuminated Y (DAY) zeolite enhanced with the augment of the Si/Al ratio in the zeolite framework [201]. The dependence of hydrophobicity on the Si/Al ratio was also presented for other zeolite structures, such as zeolite X, Y, BEA, and mordenite [202][203][204][205]. Kovo proved that A-and X-type zeolite membranes were both selective towards water because of their hydrophilicity occasioned by the high Al content, whereas the ZSM-5 membrane showed selectivity towards ethanol due to its hydrophobicity associated with the low Al content [204].…”
Section: Inorganic Membranesmentioning
confidence: 99%
“…1–4 Substituted imidazoles are a class of nitrogen-containing five-member ring system heterocycles, in which nitrogen atoms are one of the most imperative motifs established in a large number of pharmacologically active compounds and natural products. 5 Imidazoles are important bioactive heterocyclic core fragments that have proved to possess a spectrum of biological activities, covering antitumor, anti-allergic, anti-tubercular, antifungal, antibacterial, anti-biotic, anti-cancer, anti-HIV, and antiviral activities. 6 Many multi-substituted imidazoles act as p38 MAP kinase inhibitors, glucagon receptors, anti-inflammatory agents, therapeutic agents, and plant growth regulators.…”
Section: Introductionmentioning
confidence: 99%